Competitive Strategy for Media Firms : Strategic and Brand Management in Changing Media Markets. (Taylor & Francis, 2005)
Competitive Strategy for Media Firms introduces the concepts and analytical frameworks of strategic and brand management, and illustrates how they can be adapted according to the characteristics of distinct media products. Working from the premise.